Esensi Bahasa dalam Kajian Struktural - Masayu Gay (Kantor Bahasa Provinsi Maluku Utara, 2018)
This paper is the result of linguist conceptual studies that are adapted from various references and elaborated. The review is restricted to structural and not afterwards, and uses literature review. The thinking concept review is done descriptively. Beginning with Saussure, language as a form, encompasses three things (1) form-content, namely the classification of the mind and objects / objects, (2) the expression-form, ie the abstract grouping or the shadow of the sounds and forms of language . (3) content-expression, is the formation of both. The contents of this dichotomy, both on the epistemological level and its axiology. Hjemslev describes the form-content as a factor of the common sign for different languages: the form-content is seen as a type of 'meaning' which can be used as a basis for comparing different marks in differentlanguages. The forms are defined only in relation to the function of the sign, such as content-expression. The forms are forms that coincide with the form-expression, and are units that function as signs in language. From the point of view of intent, the form of content is arbitrary. Hjemslev developed the concept of sign and sign relationships. Bloomfield departs from a view of behaviorism, so that human speech can be explained by its external conditions with the mechanism. The essence of language as an expression-form looks very radical. Bloomfield builds empirical language on substance. The essence of language is the reality of the empirical structure as a means of human expression.